Transitions in the communication experiences of tracheostomised patients in intensive care: a qualitative descriptive study. Issue 15 (7th April 2015) - Flinterud, Stine Irene; Andershed, Birgitta
<x xml:space="preserve">Abstract</x> Aims and objectives To describe how tracheostomised patients in intensive care experience acts of communication and to better understand their experiences in the context of the transitions theory. Background Waking up in an intensive care unit unable to speak because of mechanical ventilation can be challenging. Communication aids are available, but patients still report difficulties communicating. Investigating how mechanically ventilated patients experience communication in the context of the transitions theory might elucidate new ways of supporting them during their transitions while being ventilated. Design A qualitative, descriptive design. Methods Eleven patients who had previously been tracheostomised in an intensive care unit were included in this quality improvement project conducted in a university hospital in Norway. Participants were tracheostomised from 3–27 days. Semistructured interviews were conducted from June 2013–August 2013, 3–18 months after hospital discharge. Transcripts were analysed using inductive content analysis. Results Participants reported a great diversity of emotions and experiences attempting to communicate while being tracheostomised. One overarching theme emerging from the analysis was the 'Experience of caring and understanding despite having uncomfortable feelings due to troublesome communication.' The theme consists of three categories. The category 'Emotionally challenging' shows that patients struggled initially. With time, their coping improved, as revealed in the category 'The experience changes with time.' Despite difficulties, participants described positive experiences, as shown in the category 'Successful communication.' Conclusion The importance of patients experiencing caring and understanding despite their difficult situation constitutes the core finding. The findings suggest that participants went through different transitions. Some reached the end of their transition, experiencing increased stability. Relevance to clinical practice Despite challenges with communication, participants reported that caring and safety provided by health care professionals were significant experiences. They viewed nonverbal communication as being very important.